From Arma to Fama: the military record of Roman republican commanders in speech and text (219-19 BC) - Bragg, E (2007)
There are three main scholarly approaches to the mechanisms by which the military record of Roman Republican commanders was disseminated in Rome: the ceremony of the triumph, the erection of monuments with their inscriptions, and finally the minting of coins. Alongside this ceremonial and material publicity this thesis investigates how and why more ephemeral media, as well as autobiographical texts, were employed to disseminate, promote and at times denigrate the Roman military record during the period of 219-19 BC. It encompasses five core chapters: introduction; oratory as praise; oratory as criticism; letters; and autobiographical prose. Chapter two argues that military achievements were orally disseminated in various contexts in Rome: it was a fundamental facet of the triumphal process; a regular part of attaining and maintaining military commands; and the military record was frequently employed in forensic defence speeches, particularly in the late Republic with the growth of the law-courts. Chapter three focuses on how and why the military record was criticised back in Rome in a variety of contexts, arguing that it was a key means by which the Roman elite regulated excessive claims of gloria. Owing in part to the increasing concerns about self-serving Roman magistrates, focusing on behaviour beyond the battlefield was a common means of undermining commanders’ military reputations. Chapter four details the heavy and regular dependence on dispatches for short-term, yet proficient, martial self-promotion. It emphasises the key role of letters in the triumphal process, including the passing of legislation aimed in part at regulating their exploitation. It also argues that private correspondence played a valuable role, particularly in the targeting of senators and other influential sections of Roman society. Chapter five investigates the role of commentaries, memoirs and historical literature in the promotion of military res gestae and how criticism alongside concerns about posterity influenced their composition. It addresses the influence of Greek biography on their composition as well as the Roman aristocratic practice of preserving correspondence and other documentation.